Age-related changes in resting energy expenditure in normal weight, overweight and obese men and women. Issue 4 (April 2015) - Siervo, Mario; Oggioni, Clio; Lara, Jose; Celis-Morales, Carlos; Mathers, John C.; Battezzati, Alberto; Leone, Alessandro; Tagliabue, Anna; Spadafranca, Angela; Bertoli, Simona
Highlights Rate and degree of age-related decline in REE is influenced by sex and body size. The rate of decline in REE was highest in obese men (slope = −8.7 ± 0.8 kcal/day/year). Age windows have been identified for the onset of the accelerated decline in REE. In women, adaptive changes appeared to occur in middle-age across all BMI groups. Adiposity appears to delay onset of adaptive changes in REE in men.